The Influence of the Treffinger Model on Critical Thinking Skills in Indonesian History Subjects: - - Aulia Meylita; Arif Permana Putra; Ana Nurhasanah (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study aims to determine the effect of Treffinger learning on critical thinking skills, subject of Indonesian history class X at MAN 4 Pandeglang. Method used is quantitative quasi-experimental type using nonequivalent control group design. The study took from May to October 2024. Hypothesis two-party t-test with the independent sample t-test, the t-test value obtained was 4.05 ≠ t-table of 1.66 with significance level 0.05. Statistical "4.05> 1.66", H_(0 ) is rejected H_(a ) is accepted, concluding there is an effect of Treffinger model on critical thinking skills. Average posttest score for experimental class was 77.17, and control class was 70.00, indicating experimental class using the Treffinger model had a higher average score than the control class. Treffinger learning can be used as a reference in learning to be able to understand concepts, play an active role in learning, and develop thinking skills to improve critical thinking skills according to Ennis indicators.